Keubudiyahan and Religious Activities Perspective KH. Shodiq Mahmud in Efforts to Internalize Ibadurrahman Values at Al Jauhar Jember Islamic Boarding School - Akmalia, Rizka Tamara; Tsauri, Sofyan; Subakri, Subakri (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Jember is one of the education cities in Indonesia where there are various universities there. So that students in Jember Regency are required to have a strong mentality and condition in dealing with environmental changes that occur there. Most changes in the surrounding environment can lead to bad things so that this can affect the future of students as the next generation of the nation. Like the many acts of pornography and pornography and the existence of radical Islamic thoughts among students, this can result in the erosion of Islamic values and faith in higher education circles. Pondok Pesantren, which incidentally is a place for authentic Islamic scientific treasures, can be a solution to the problems that have occurred so far. Therefore, this study reveals concrete evidence of the influence of optimizing cultural and religious activities in the context of internalizing ibadurrahman values which are part of the vision and mission of the caretaker of Al Jauhar Islamic Boarding School, namely KH. Shodiq Mahmud. Based on the results of the study, that there are several activities contained in the twelve characteristics of ibadurrahman . The values of ibadurrahman are expected to be able to influence santri (students) in strengthening Islamic values and achieving life goals that are blessed by Allah SWT